Ability of university-level education to prevent age-related decline in emotional intelligence - Cabello, Rosario; Navarro, Beatriz; Latorre, Jose Miguel; Fernández-Berrocal, Pablo (Frontiers in Aging Neuroscience, 2014)
Numerous studies have suggested that educational history, as a proxy measure of active cognitive reserve, protects against age-related cognitive decline and risk of dementia. Whether educational history also protects against age-related decline in emotional intelligence (EI) is unclear. The present study examined ability EI in 310 healthy adults ranging in age from 18 to 76 years using the Mayer–Salovey–Caruso Emotional Intelligence Test (MSCEIT). We found that older people had lower scores than younger people for total EI and for the EI branches of perceiving, facilitating and understanding emotions, whereas age was not associated with the EI branch of managing emotions. We also found that educational history protects against this age-related EI decline by mediating the relationship between age and EI. In particular, the EI scores of older adults with a university education were higher than those of older adults with primary or secondary education, and similar to those of younger adults of any education level. These findings suggest that the cognitive reserve hypothesis, which states that individual differences in cognitive processes as a function of lifetime intellectual activities explain differential susceptibility to functional impairment in the presence of age-related changes and brain pathology, applies also to EI, and that education can help preserve cognitive-emotional structures during aging.